2015
DOI: 10.3846/16484142.2015.1048721
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Urban Public Transport Websites According to Extent of Provided Information

Abstract: This paper is based on the analysis of websites of Urban Public Transport (UPT) made in different states. The paper proposes a standard of ‘minimal information websites content’ named as ‘Passenger Friendly Web’. Information content is divided into a set of elements. Their weights are determined by expert evaluation with the support of mathematics, especially of Saaty’s Method. Possibilities for future research are also regarded. Results can be applied to all Internet websites of UPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The smallest value of the concordance coefficient W min , with the significance level α = 0.01 and the degree of freedom ν = n − 1 = 15 − 1 = 14, allowing the authors to assume that the respondents' estimates were consistent, was calculated by Equation (9). The smallest value of the concordance coefficient W min = 0.0400 corresponded to only about one-fifth of the calculated concordance coefficient W = 0.194.…”
Section: Calculating the Average Rank The Consistency Of Expert Estim...mentioning
confidence: 99%
See 1 more Smart Citation
“…The smallest value of the concordance coefficient W min , with the significance level α = 0.01 and the degree of freedom ν = n − 1 = 15 − 1 = 14, allowing the authors to assume that the respondents' estimates were consistent, was calculated by Equation (9). The smallest value of the concordance coefficient W min = 0.0400 corresponded to only about one-fifth of the calculated concordance coefficient W = 0.194.…”
Section: Calculating the Average Rank The Consistency Of Expert Estim...mentioning
confidence: 99%
“…Experience has shown that passengers usually choose the mode of transport that best suits their personal needs, habits and understanding of the expected quality of traveling. The mode of transport that is the most acceptable to a passenger can be determined by developing a system of criteria and calculating their weights using multi-criteria decision-making (MCDM) methods [5][6][7][8][9]. Passenger loyalty development increases the profits of airline, rail, and road transport companies.…”
Section: Introductionmentioning
confidence: 99%
“…Since websites include multilevel data, evaluation may be carried through different perspectives and samplings. There are several methodologies offered in literature such as content analysis (Kwon and Jeong, 2015), analytic hierarchical process (Bulíček and Drdla, 2015;Ecer, 2014), benchmarking (Johnson and Misic, 1999), decision tree (Sun et al, 2015), balanced scorecard (Kline et al, 2004), quality function deployment (Gonzalez et al, 2015), delphi method (Leite et al, 2014) etc. Though, no agreed method exists (Sun et al, 2015;Law and Buhalis, 2010).…”
Section: How To Evaluate Corporate Websitesmentioning
confidence: 99%
“…Since there are various sectors, there are also several websites specialized for different purposes. Some researchers focus on the evaluation of websites serving in a specific area such as e-commerce (Kang et al, 2016), travel and tourism (Law and Bhalis, 2010;Cengiz and Akkuş, 2015), sports (Chiu and Won, 2016), logistics (Bulíček and Drdla, 2015;Jain and Rangnekar, 2015) and health (Raj et al, 2016). Websites are evaluated according to various criteria which are sector specific for some cases.…”
Section: Dimensions Of Website Evaluationmentioning
confidence: 99%